2012
DOI: 10.1073/pnas.1201807109
|View full text |Cite|
|
Sign up to set email alerts
|

Energy landscape and multiroute folding of topologically complex proteins adenylate kinase and 2ouf-knot

Abstract: While fast folding of small proteins has been relatively well characterized by experiments and theories, much less is known for slow folding of larger proteins, for which recent experiments suggested quite complex and rich folding behaviors. Here, we address how the energy landscape theory can be applied to these slow folding reactions. Combining the perfect-funnel approximation with a multiscale method, we first extended our previous atomic-interaction based coarse grained (AICG) model to take into account lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 46 publications
(50 reference statements)
11
172
0
1
Order By: Relevance
“…Whereas the multiplicity and flexibility of folding pathways have been investigated for multidomain proteins (3,4,15,16,33), questions still remain, particularly with regard to how the different types of folding mechanisms of multidomain proteins, folding through multiple or flexible pathways, or folding along a single sequential pathway can be distinguished from the energy landscape perspective. Using a simple structurebased model, we have shown that the folding mechanism is determined by the balance between the tendency to prevent the steep decrease of entropy through the association of discontinuous parts of the chain and the tendency to promote energy stabilization through the formation of compact domains.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the multiplicity and flexibility of folding pathways have been investigated for multidomain proteins (3,4,15,16,33), questions still remain, particularly with regard to how the different types of folding mechanisms of multidomain proteins, folding through multiple or flexible pathways, or folding along a single sequential pathway can be distinguished from the energy landscape perspective. Using a simple structurebased model, we have shown that the folding mechanism is determined by the balance between the tendency to prevent the steep decrease of entropy through the association of discontinuous parts of the chain and the tendency to promote energy stabilization through the formation of compact domains.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…folding intermediates | internal friction | eWSME model T opology of protein conformation, or the spatial arrangement of structural units and the chain connectivity among them, is a key determinant of the folding mechanisms of proteins (1)(2)(3)(4)(5). However, predicting a folding pathway is a subtle problem when a protein comprises multiple regions of cooperative structure formation (i.e., foldons or domains).…”
mentioning
confidence: 99%
“…In addition, when the folding process reaches the glass transition state, the intermediates have only a few paths towards the native structure [61]. It is worth noting that although the folding funnel model was established originally based on studies of small and fast-folding proteins, it can also be used to describe and explain the folding process of large and complex proteins [64].…”
Section: Folding Process and Pathwaysmentioning
confidence: 99%
“…Our simulations in the initial part used coarse-grained models where each amino acid in proteins was modeled by one particle located at Cα position (34) and each nucleotide in DNA was represented by three particles, each representing sugar, phosphate, and base (35,36). The protein energy function is based on native structure information at atomic resolution (SI Appendix, SI Methods provides details).…”
Section: Resultsmentioning
confidence: 99%